10.37304 Makna Dan Simbolisme Verbal Dalam Tradisi Kematian Mitungdina, Matangpuluh Nyatus, Dan Nyewu Di Desa Sriwulan Kecamatan Sayung - Adinda Rizka Aulia Putri; Weni Destrianti Zhaputri; Imam Baehaqie (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
Language is a system of sound symbols that society uses for communication and as a reflection of cultural values and group identity. This study aims to analyze the meanings and verbal symbolism found in the death rituals of mitungdina, matangpuluh, nyatus, and nyewu in Sriwulan Village, Sayung District. The research method employed is descriptive qualitative, utilizing techniques such as interviews, participant observation, and recordings. The data sources for this study include both primary and secondary data. The findings indicate that each stage of the rituals encompasses religious, social, and symbolic values, which are expressed through prayer recitations, traditional foods like apem, and the preservation of Javanese culture intertwined with Islamic teachings.